The Effect of Work Stress on Employees Performance Through Work Motivation on Employees of Municipal Waterworks - Nur Hidayah, Atika; Hariri Agus Prohimi, Afwan (Adpebi Science Series, 2022)
This study aims to determine the effect of work stress on employee performance through work motivation. This research is a quantitative research with descriptive and explanatory research design. The population in this study were employees of PDAM Blitar City. The sample taken in this study were 42 respondents. using the census method. Then test the feasibility of the instrument using validity and reliability tests. The analysis technique used descriptive statistical analysis and Partial Least Square (PLS) analytic. The results of this study indicate that Job Stress on Employee Performance, then Work Motivation on Employee Performance, then Work Stress on Work Motivation, and Work Stress on Employee Performance Through Work Motivation has a positive, indirect and significant effect.